2006
DOI: 10.1136/bmj.38740.614954.55
|View full text |Cite|
|
Sign up to set email alerts
|

Factors influencing death at home in terminally ill patients with cancer: systematic review

Abstract: Objectives To determine the relative influence of different factors on place of death in patients with cancer. Data sources Four electronic databases-Medline , PsycINFO (1972PsycINFO ( -2004, CINAHL (1982-2004), and ASSIA (1987-2004; previous contacts with key experts; hand search of six relevant journals. Review methodsWe generated a conceptual model, against which studies were analysed. Included studies had original data on risk factors for place of death among patients, > 80% of whom had cancer. Strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

57
882
10
38

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 849 publications
(987 citation statements)
references
References 62 publications
57
882
10
38
Order By: Relevance
“…1 However, the actual place of death results from a complex interrelationship of individual and environmental factors. 2 In contrast to northern European countries, Italian caregivers are mostly relatives, rather than friends or neighbors. As a consequence, cultural and social attitudes, deficiencies in the health care facilities, or family structure may strongly influence the place of death in a country like Italy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 However, the actual place of death results from a complex interrelationship of individual and environmental factors. 2 In contrast to northern European countries, Italian caregivers are mostly relatives, rather than friends or neighbors. As a consequence, cultural and social attitudes, deficiencies in the health care facilities, or family structure may strongly influence the place of death in a country like Italy.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has shown that six factors were strongly associated with home death: patient's low functional status, their preferences, home care and its intensity, living with relatives, and extended family support. 2 Patient preference as to place of death, level of caregiver support and entitlement to private shift nursing were significantly associated with patients dying at home. 3 However, the complex process of decision making about the place of death is often dynamic and contradictory, 4 and involves the patient, the caregivers, and the professionals, 5 as well as environmental factors including hospital or hospice facilities.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Data also suggest that most people with advanced illnesses prefer to be cared for and death at home or near their home (Tang, 2003;Gomes and Higginson, 2006). Yet, most people die in institutions or if at home, without the appropriate level of care needed to meet their basic needs (Kikule, 2003, Docherty et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Wir sterben mehrheitlich in Organisationen, in Krankenhäusern und Pflegeheimen. Internationale Vergleiche zeigen, dass das Ausmaß der Institutionalisierung des Sterbens weiter zuund somit das Sterben zu Hause weiter abnimmt [28,29].…”
Section: Introductionunclassified